2000
DOI: 10.1094/pdis.2000.84.12.1319
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shredding or Treating Apple Leaf Litter with Urea on Ascospore Dose ofVenturia inaequalisand Disease Buildup

Abstract: Ascospores produced on diseased leaves in the leaf litter constitute the primary inoculum causing scab in commercial apple orchards in the northeastern United States. Two sanitation practices, shredding the leaf litter with a flail mower and urea application, were evaluated for their potential to reduce the risk of primary scab. Three measures of a treatment's potential were made: leaf litter density was evaluated to determine reduction of the source or primary inoculum; trapped ascospores were counted to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 16 publications
3
55
0
1
Order By: Relevance
“…Populin had a similar effect as synthetic fungicides on both Golden and Jonathan in the second year (under wet climate conditions). The repeated application of synthetic fungicides throughout the growing season has been the only approach to managing apple scab (Sutton et al, 2000). According to Rosenberger and Cox (2010), several factors may enable ascosporous infection to become established in early spring and then progress during summer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Populin had a similar effect as synthetic fungicides on both Golden and Jonathan in the second year (under wet climate conditions). The repeated application of synthetic fungicides throughout the growing season has been the only approach to managing apple scab (Sutton et al, 2000). According to Rosenberger and Cox (2010), several factors may enable ascosporous infection to become established in early spring and then progress during summer.…”
Section: Discussionmentioning
confidence: 99%
“…As our first populin applications were carried out in the early vegetation period, the populin treatment probably also had noxious effects on overwintering ascospores. Ascospores produced by sexual reproduction in the leaf litter constitute the primary inoculum causing scab in commercial apple orchards (Sutton et al, 2000). Populin application to the trees in autumn before leaf fall would probably further reduce the following year's scab infestation; however, further experiments in this direction need to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the effects of sanitary practices such as burning or burying leaves in the soil (Gomez et al, 2004), leaf shredding (Vincent et al, 2004;Holbet al, 2006) and a combination of shredding and using urea (Sutton et al, 2000) on reducing scab inoculum.These studies showed an ascosporic inoculum reduction of between 40 and 95% and a correlated scab reduction of 45 to 85%.Collecting leaves from the ground in the inter-rows in autumn along with burying the leaves left along the row has a positive effect in reducing primary contamination (Gomez etal., 2004). Gomez et al (2004) showed that for two consecutive years the practice of 'raking and ridging' reduced the severity of scab on the fruit by 68 to 74%, depending on the year.…”
Section: 2inoculum Reductionmentioning
confidence: 99%
“…The fungicidal properties of bicarbonates have long been known (Clayton et al, 1943) Sutton et al (2000) observed that in general, growers do not use sanitation techniques, although they can result in significant reductions in ascospore load. Reluctance to use sanitation practices is through:  the need for specialized equipment (shredder),  the failure of sanitation to provide complete disease control, and  lack of reliable relationships between sanitation measures and the degree to which fungicides can be reduced the following year.…”
Section: Bicarbonate Saltsmentioning
confidence: 99%
See 1 more Smart Citation